Persistent Organic Pollutants in Tagus Estuary Salt Marshes: Patterns of Contamination and Plant Uptake - Ricardo Cruz de Carvalho; João Cardoso; João Albuquerque Carreiras; Paula Santos; Carla Palma; Bernardo Duarte (MDPI AG, 2024)
The presence of anthropogenic compounds, including organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs), was studied in three salt marshes within the Tagus estuary, Portugal, along an anthropogenic pressure gradient. Results revealed differences in OCPs and PCBs among the marshes, with differing concentration levels. Specifically, one marsh, with surrounding agricultural activity, showed the highest OCP concentrations, while another, with a historical industrial past, exhibited elevated PCB levels. In contrast, a third marsh, part of a natural reserve, displayed comparatively lower concentrations of both substances. Sediment concentrations, likely influenced by agricultural practices, were found to be comparable to or higher than those observed in other Portuguese estuaries. The halophyte Spartina maritima was found to absorb OCPs, particularly in its aboveground tissues, suggesting bioaccumulation within the plant. Additionally, PCB levels appeared to be influenced by industrial history, with one marsh displaying notably higher concentrations. In conclusion, the persistence of organochlorine compounds in the salt marsh ecosystems notwithstanding the regulatory prohibitions implemented in the 1990s highlights the need for continuous monitoring and study of such sites and the necessity of remediation practices, which are imperative to mitigate ecological and health risks in these polluted salt marshes.